Bilateral concentric and eccentric isokinetic strength evaluation of quadriceps and hamstrings in basketball players - Hadzic, V.; Erculj, F.; Bracic, M.; Dervisevic, E. (Collegium Antropologicum, 2013)
The aim of the study was to investigate the existence of bilateral asymmetry in healthy basketball players of different age, as evidence suggest that it may be an age related phenomenon which develops over the years of training. Fifty healthy basketball players (26 males and 24 females) participated in the study. The quadriceps (Q) and the hamstring (H) were tested concentrically and eccentrically at 60°/s. The main outcome measure was body weight normalized peak torque (PT/BW). We have also calculated different strength ratios as well as the bilateral strength differences. The main findings indicate that (1) bilateral strength asymmetry is noticeable in senior basketball players relating predominantly to the Q (2) some gender related strength differences were mainly associated with the concentric strength of Q and H (3) when corrected for weight and height, age related strength differences were relatively small and observed only with respect to H strength in males (4) superiority of eccentric over concentric strength values of Q and H was more pronounced in females than in males. Strength asymmetry in senior basketball players may be more attributable to the better neuromuscular control during vertical jumping than to the strength itself, as there were no age related differences between cadets and senior players.